Hak Anak-Anak Pengungsi Rohingya dan Perlakuan Standar Minimum dalam Hukum Internasional - Lesbatta, Franszisco Alvaro; Hanafi, Irma Halima; Daties, Dyah Ridhul Airin (Faculty of Law Universitas Pattimura, 2024)
The Rohingya ethnic group was excluded by the Myanmar Military Junta Government from the list of majority ethnic groups and ethnic minorities who have lived in Myanmar since the 1980s. Since then, the Rohingya ethnic group has become victims of discrimination, forced labor, human rights violations and so on. This resulted in the Rohingya ethnic group seeking refuge in other countries, including Bangladesh, Malaysia, Thailand, India and Indonesia. Rohingya ethnic refugees entered Indonesia for the first time in 2009. The surge in Rohingya refugees entering Indonesia occurred in the period November 2023 to 10 December 2023, where they used 9 different boats. Fulfilling the rights of Rohingya refugee children is not yet sufficient or has not been fulfilled optimally in accordance with the 1989 Convention on the Rights of the Child which is specifically stated in Article 22 which stipulates that every international and national element must guarantee the fulfillment of the rights of children with refugee status. The research method uses normative juridical research, with an analytical perspective research type, as well as sources of legal materials which include primary legal materials, secondary legal materials and tertiary legal materials. Collection of legal materials is carried out through literature study and analysis. The research results show that Indonesia has tried to fulfill the rights of Rohingya refugee children, but this has not been implemented well or optimally. So that Indonesia, as one of the countries that has ratified the 1989 Convention on the Rights of the Child, must make more efforts to fulfill the rights of Rohingya refugee children in accordance with the Convention on the Rights of the Child which is specifically stated in article 22, and must be in line with the concept of minimum child protection standards. which is a guideline in protecting and fulfilling the rights of Rohingya refugee children.